The study of chromosomal aberrations in mice infested with radiated and non-radiated protoscolices of Echinococcus granulosus . (مجلة ديالى للبحوث الانسانية, 2022)
The mitotic index (MI) and the chromosomal aberration in cells have been studied in white bulb mice subjected to radiated and non-radiated protosolices of E. granulosis . In this experimental infestation , gamma ray of 81.58416 × 103 wave length have been used. The protoscolices were subjected to a high degree of 25 Gy and low degree of 5 Gy. The results revealed no significant variation in both MI and chromosomal aberration were found in bone marrow cells of infested mice in comparison to control.